2011
DOI: 10.1245/s10434-011-2195-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Microinvasion of Small Hepatocellular Carcinoma ≤2 cm

Abstract: Even in cases of HCC ≤ 2 cm, patients who are suspected of having invasive gross type tumors in preoperative imaging diagnosis or who have a high DCP level (>100 mAU/ml) are at risk for MI. Therefore, in such patients, hepatic resection with a wide tumor margin should be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
124
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(140 citation statements)
references
References 36 publications
14
124
2
Order By: Relevance
“…AFP-L3 positivity and failure of AFP-L3 conversion to negativity or further elevation of AFP-L3 are associated with aggressive tumor behavior and worse histologic grade results in early tumor recurrence (i.e., in MVI) (28, 33). In a different study, DCP >100 mAU/mL was proposed as a reliable predictor for MVI even in small HCCs (≤2 cm), with a positive predictive value of 79.3% (34). They also reported that DCP was more specific than AFP for MVI (34).…”
Section: Tumor Markersmentioning
confidence: 97%
See 1 more Smart Citation
“…AFP-L3 positivity and failure of AFP-L3 conversion to negativity or further elevation of AFP-L3 are associated with aggressive tumor behavior and worse histologic grade results in early tumor recurrence (i.e., in MVI) (28, 33). In a different study, DCP >100 mAU/mL was proposed as a reliable predictor for MVI even in small HCCs (≤2 cm), with a positive predictive value of 79.3% (34). They also reported that DCP was more specific than AFP for MVI (34).…”
Section: Tumor Markersmentioning
confidence: 97%
“…In a different study, DCP >100 mAU/mL was proposed as a reliable predictor for MVI even in small HCCs (≤2 cm), with a positive predictive value of 79.3% (34). They also reported that DCP was more specific than AFP for MVI (34).…”
Section: Tumor Markersmentioning
confidence: 97%
“…But, the accuracy of DCP might be diminished in prolonged obstructive jaundice, intrahepatic cholestasis with vitamin K deficiency, and intake of warfarin and even some antibiotics [4]. Thirdly, DCP might be a better marker than AFP in detecting early stage of HCC with tumors smaller than 2 cm [4,59]. Fourthly, the half-life of plasma DCP around 40-72 hours is much shorter than that of AFP around 5-7 days.…”
Section: The Significance and Marker For Hcc Diagnosismentioning
confidence: 99%
“…In Table 1, laboratory data, imaging data, and pathological data have identified some indicators as risk factors of prognosis for sufferers with HCC (12)(13)(14)(15). Microvascular invasion (MVI), tumor size, and tumor number indicated in imaging data are considered as risk factors for prognosis.…”
Section: Ggt As a Predictive Biomarker In Clinical Investigationsmentioning
confidence: 99%